Orchestrating Green HRM and Green Marketing Capability through Green Innovation for Sustainable Marketing Performance: An East Java SME Framework - Abdul Ghofur; Muhamad Imam Syairozi (Lembaga Publikasi Ilmiah Nusantara, 2025)
Sustainable marketing performance in small and medium-sized enterprises (SMEs) requires coordination between internal employee systems and external market-facing capabilities. This conceptual and methodological paper develops a capability-orchestration framework linking green human resource management (GHRM), green marketing capability (GMC), green innovation (GI), and sustainable marketing performance (SMP) in the context of East Java SMEs. The natural-resource-based view identifies the strategic value of environmentally oriented resources; the ability–motivation–opportunity perspective explains how GHRM builds employee ability, motivation, and opportunity; and dynamic-capability logic explains how GMC senses and responds to green market change. GI is proposed as the shared conversion mechanism that combines these capabilities into market-relevant environmental improvements. To demonstrate the instrument architecture and the PLS-SEM workflow rather than to test empirical relationships, the paper employs a transparent synthetic dataset consisting of 250 simulated cases and 21 reflective indicators. The simulation produces internally consistent reliability, validity, structural path, mediation, and predictive results. However, no actual owner-managers or SMEs were surveyed, and the numerical results should not be interpreted as empirical evidence for East Java SMEs. The contribution is therefore theoretical and methodological: it specifies capability orchestration across HR, marketing, and innovation domains, distinguishes SMP from broad firm-performance outcomes, and provides an empirically testable instrument and analysis protocol for future field research. Any managerial or policy implications remain conditional on validation with genuine field data.